Community based integrated intervention for prevention and management of chronic obstructive pulmonary disease (COPD) in Guangdong, China: cluster randomised controlled trial. (1st December 2010) - Zhou, Yumin; Hu, Guoping; Wang, Dali; Wang, Shaoyi; Wang, Yujun; Liu, Zhigang; Hu, Jinxin; Shi, Zhe; Peng, Gongyong; Liu, Shengming; Lu, Jiachun; Zheng, Jingping; et al.
Abstract : Objective To evaluate the effects of a community based integrated intervention for early prevention and management of chronic obstructive pulmonary disease (COPD) in China. Design Cluster randomised controlled trial. Setting Eight healthcare units in two communities. Participants Of 1062 people aged 40-89, 872 (101 with COPD and 771 without COPD) who fulfilled the inclusion and exclusion criteria were allocated to the intervention or the usual care programmes. Intervention Participants randomly assigned to integrated intervention (systematic health education, intensive and individualised intervention, treatment, and rehabilitation) or usual care. Main outcome measures Annual rate of decline in forced expiratory rate in one second (FEV1 ) before use of bronchodilator. Results Annual rate of decline in FEV1 was significantly lower in the intervention community than the control community, with an adjusted difference of 19 ml/year (95% confidence interval 3 to 36) and 0.9% (0.1% to 1.8%) of predicted values (all P<0.05), as well as a lower annual rate of decline in FEV1 /FVC (forced vital capacity) ratio (adjusted difference 0.6% (0.1% to 1.2%) P=0.029). There were also higher rates of smoking cessation (21% v 8%, P<0.004) and lower cumulative death rates from all causes (1% v 3%, P<0.009) in the intervention community than in the control community during the four year follow-up. Improvements in knowledge of COPD and smoking hazards, outdoor air quality, environmental tobacco smoke, and working conditions were also achieved (all P<0.05). The difference in cumulative incidence rate of COPD (both around 4%) and cumulative death rate from COPD (2% v 11%) did not reach significance between the two communities. Conclusions A community based integrated intervention can have a significant impact on the prevention and management of COPD, mainly reflected in the annual rate of decline in FEV1 . Trial registration Chinese Clinical Trials Registration (ChiCTR-TRC-00000532).